A Systematic Mapping Study on Software Architecture Recovery - Çatal, Çağatay; BAYDOĞMUŞ, GÖZDE KARATAŞ (My University, 2016)
In this study, we investigated the approaches used in software architecture recovery papers, identify the current status of paper distributions in terms of year, publication channel, electronic databases, and journals. We executed a mapping study to cluster the software architecture recovery research papers. Papers published since 2000 have been used for this study. The following databases were investigated: Wiley, IEEE, ACM, Science Direct. Our search accessed 250 papers, but after in-depth analysis, 60 papers were found to be related to the software architecture recovery area. Our study shows that there exist many architecture recovery approaches in the literature, with machine learning-based techniques dominating the field. On the basis of this study, we suggest researchers develop more model centric software architecture recovery approaches because of model driven development’s popularity in software engineering field.
Keywords: software architecture; architecture recovery; architectural erosion; architectural drift